P075 Long COVID is associated with poor mental health in patients with rheumatic disease: results from a 14-month longitudinal study. (23rd April 2022) - Cox, Natasha; Raizada, Sabrina R; Barkham, Nick; Bateman, James
Abstract: Background/Aims: COVID-19 has had severe consequences across the globe and the detrimental impacts are continually emerging. Recently it has been recognised that some patients develop persisting symptoms past the initial infection, termed 'long-COVID'. The prevalence of long-COVID in the general population is estimated to range from 2.3% to 37.7% and while risk factors in this group have been explored, there is a lack of data reporting prevalence and risk factors of long-COVID in patients with rheumatic disease (RD). This is an interim report of an ongoing study (clinicaltrials.gov NCT04542031) exploring COVID19 in patients with RD; we report risk factors for the development and impacts on health-related quality of life (HRQoL) of long-COVID in patients with RD to inform guidelines and target service provision as the pandemic continues. Methods: We distributed three web-based surveys spanning 14 months, April 2020 to June 2021. Surveys were communicated via a linked SMS-text message; all patients with a validated mobile-number under rheumatology follow-up at the Royal Wolverhampton Trust were invited to participate in survey-1, those that consented were invited to participate in follow-up surveys. Patients reported a range of metrics including demographics, and self-reported COVID-status; on completion patients were asked to complete a validated HRQoL survey, the short-Form 12 encompassing physical (PCS), and mental component (MCS) scores. Data were collected 7-days following survey distribution. SPSS version-27 was used for comparative data analysis. Results: Initial surveys were sent to 7911 active follow-up patients, 1636/7911 (21%) responded and consented to further follow-up; 628/1636 (38%) responded to all surveys. 45/628 (7%) reported contracting COVID at any time (59years, female-80%, BAME-9%). 26/45 (58%) suffered acute-COVID (symptoms <4weeks), and 19 (42%) suffered long-COVID (symptoms 4 weeks or more); 10/19 (53%) had post-COVID syndrome (symptoms 12 weeks or more). Compared to the acute-COVID group more in the post-COVID syndrome group were female (69% vs 100%), BAME (4% vs 20%), housebound due to pre-pandemic ill-health (5% vs 60%), and needed regular assistance (7% vs 60%). While baseline MCS did not differ, after 14months, compared to the acute-COVID group MCS was significantly worse in those that developed post-COVID syndrome (43.2 vs 35.8) and more in this group reported visiting their GP due to mental health concerns (7% vs 30%). Age, diagnosis, and PCS were similar across groups. Conclusion: These data highlight that in RD patients those at risk of developing post-COVID syndrome are females, those with worse pre-pandemic health, and BAME-groups. While physical health remained stable, following infection the mental health of patients that developed post-COVID syndrome was significantly worse than those that suffered COVID acute-COVID. These data can be used to identify COVID-positive patients at greater risk of developing post-COVID syndrome and suggest services need to adapt to support psychological well-being in these groups. Disclosure: N. Cox: None. S.R. Raizada: None. N. Barkham: None. J. Bateman: None.